Prevalência da Síndrome Respiratória Aguda Grave causada pelo SARS-COV-2 e fatores associados ao óbito em paciente internados na Paraíba - Silva, Allan Batista (2023)
Introduction: SARS-CoV-2, a new type of coronavirus, is the etiological agent of Covid19. The first cases emerged in the city of Wuhan, China, in December 2019, and soon spread across the world. Due to its high pathogenicity and easy transmission, the pandemic caused by SARS-CoV-2 is recognized as the most serious health crisis experienced by everyone in the world in recent times. Objective: To analyze the prevalence of SARS caused by SARS-CoV-2 and risk factors associated with the death of people hospitalized in the State of Paraíba, Brazil. Method: This is an observational, cross-sectional, retrospective study, with a quantitative approach, carried out from data registered, between January 9, 2021 and March 10, 2022, by the Health Department of the State of Paraíba about the cases of hospitalization for SARS caused by SARS-CoV2. The sample is of the non-probabilistic type, consisting of 1,431 cases of individuals hospitalized with the disease. Data were tabulated and analyzed in the R software, where the multiple logistic regression model was applied, in order to verify the association between the outcome variable death and the other variables under study. In addition, Odds Ratio (OR) estimates and their respective confidence intervals were obtained. The research was approved by the Research Ethics Committee of the Federal University of Paraíba, under protocol number 4,563,930. Results: Of the total number of investigated cases, it was observed that the majority occurred in males (54.16%), aged up to 59 years (50.24%), of mixed skin color/race (83, 72%), education in the 1st to 5th year of Elementary School (28.23%), residents of the urban area (87.56%). The number of SARS cases caused by SARS-CoV-2 is distributed throughout the state of Paraíba, being more prevalent in the Intermediate Geographic Region of João Pessoa, with 892 (62.33%) of the records. In the present study, only 855 (59.75%) progressed to cure, while 576 (40.25%) died from the disease. From the logistic regression model, it was possible to identify that individuals aged 60 years or older are 59.2% less likely to evolve to death than individuals aged up to 59 years. Individuals with respiratory distress are 1.56 times more likely to die than those who do not have such a symptom. As for ICU admission, the model estimated that people hospitalized in this sector are 4.39 times more likely to evolve to death than those who did not need this type of hospitalization. Individuals who used invasive mechanical ventilation were 15.22 times more likely to die from SARS caused by Covid-19 than those who did not need this ventilatory support. Final considerations: In light of the above, it was found that SARS caused by covid-19 was well distributed in Paraíba and that there are factors that are related to death, such as age group, presence of respiratory distress, need for ICU admission and ventilatory support.